THE HISTORICAL-EPISTEMOLOGICAL CONSTRUCTION OF THE HASAN HADITH: Al-Tirmidhi's Methodological Innovation - Muhammad, Muhammad Doktor; Solihin, Nik Muhammad Bin Nik Mohamed Amin (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
This study examines the historical context and intellectual rationale behind Imam al-Tirmidhi’s formulation of the hasan hadith category, a significant methodological innovation that emerged in response to the limitations of the prevailing sahih–da‘if dichotomy in the formative period of Hadith scholarship. The research focuses on the dynamics of hadith transmission during the second and third centuries AH, a period characterized by the expansion of transmission networks, varying levels of narrator reliability, and the circulation of numerous reports that could not be adequately classified as either fully authentic or entirely weak. Employing a historical and comparative approach through an extensive review of primary and secondary sources, this study investigates the disciplinary needs that motivated al-Tirmidhi’s conceptualization of the hasan category and explores its role in organizing the increasingly heterogeneous body of hadith literature. The findings demonstrate that the emergence of the hasan category constituted a methodological response to the intellectual realities of the Abbasid era, providing an intermediate classification for narrations that occupied a position between acceptance and rejection. This innovation clarified evaluative boundaries, facilitated a more systematic management of the expanding hadith corpus, and contributed to the refinement of hadith criticism. The academic contribution of this study lies in its reinterpretation of the hasan category not merely as a technical classification but as an adaptive epistemological framework shaped by historical necessity, thereby offering a deeper understanding of the relationship between socio-intellectual developments and the evolution of ‘ilm mustalah al-hadith. Penelitian ini mengkaji konteks historis dan rasionalitas intelektual di balik perumusan kategori hadis hasan oleh Imam al-Tirmidzi, yang merupakan salah satu inovasi metodologis penting dalam perkembangan ilmu hadis. Kategori ini muncul sebagai respons terhadap keterbatasan dikotomi sahih–da‘if yang mendominasi fase awal kajian hadis. Fokus penelitian diarahkan pada dinamika transmisi hadis pada abad ke-2 dan ke-3 H, suatu periode yang ditandai oleh meluasnya jaringan periwayatan, beragamnya tingkat kredibilitas para perawi, serta beredarnya banyak riwayat yang tidak dapat diklasifikasikan secara memadai sebagai hadis yang sepenuhnya sahih maupun sepenuhnya da‘if. Dengan menggunakan pendekatan historis dan komparatif melalui telaah literatur terhadap sumber-sumber primer dan sekunder yang relevan, penelitian ini bertujuan menjelaskan kebutuhan keilmuan yang melatarbelakangi lahirnya kategori hasan serta menganalisis perannya dalam menata korpus hadis yang semakin heterogen. Hasil penelitian menunjukkan bahwa kemunculan kategori hasan merupakan solusi metodologis terhadap realitas intelektual pada era Abbasiyah, dengan menyediakan ruang klasifikasi menengah bagi riwayat-riwayat yang berada di antara penerimaan dan penolakan. Inovasi ini memperjelas batas-batas evaluatif dalam kritik hadis, memfasilitasi pengelolaan korpus hadis yang terus berkembang secara lebih sistematis, serta berkontribusi pada penyempurnaan metodologi kritik hadis. Kontribusi akademik penelitian ini terletak pada reinterpretasi kategori hasan bukan semata-mata sebagai klasifikasi teknis, melainkan sebagai kerangka epistemologis yang adaptif dan lahir dari kebutuhan historis, sehingga memberikan pemahaman yang lebih mendalam mengenai hubungan antara perkembangan sosial-intelektual dengan evolusi ‘ilm mustalah al-hadith.